Dynamics of Governance and Private Partnership in Social Programme Implementation: A Comparative Study-Regency of Sinjai, Takalar and Bantaeng in Indonesia - Rusliadi, Rusliadi; Lestari, Dian; Amiruddin, Iswadi; Puspita, Dian Permata (Jurnal Pemerintahan dan Politik Lokal, 2024)
This study aims to identify and analyze the collaboration between the government and the private sector in managing non-cash basic food assistance programs in three Regencies in Indonesia, namely Sinjai, Takalar, and Bantaeng Regencies. The program in the food sector began in 1998, aimed at ensuring the availability of rice at affordable prices for the poor, known as the Non-Cash Food Assistance program (Bantuan Pangan Non-Tunai, BPNT). It is hoped that the parties that cooperate in the delivery of the Non-Cash Food Assistance program (Bantuan Pangan Non-Tunai, BPNT) services will develop collaborative partnerships and depend on regional readiness. On the other hand, this has a negative impact because implementers in the regions are more flexible in controlling without oversight from the central government. Using a multi-case approach, this research employs a qualitative-explorative research method to examine Indonesia's non-cash food assistance program as a national initiative to fight poverty. Data was collected from interviews, field observations and applicable literature, then Nvivo 12 Pro was used to analyze the results. The study findings show that cooperation between the public and private sectors in the regions in implementing the basic food assistance program is still not optimal. The practice of corruption in program implementation is still an obstacle to implementation. Society accepts not according to the provisions, and the quality of commodities is far from expectations.